2002
DOI: 10.3354/ame029227
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of bacterial production, respiration and growth efficiency in the open NW Mediterranean Sea

Abstract: Bacterial growth efficiency (BGE) can have a major influence on planktonic food web structure and function; however, its controlling factors are poorly understood. Here, we report results from an annual study aimed at examining bacterial respiration (BR), production (BP), biomass (BB) and BGE in the upper 130 m of the DYFAMED station (JGOFS site, France) in the NW Mediterranean Sea. From the pre-bloom period to early summer, and with a negative gradient from sub-surface to 130 m, bacterial parameters seem to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
96
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 46 publications
15
96
2
1
Order By: Relevance
“…[dFe] [Bonnet and Guieu, 2006], TChla [Marty et al, 2002], BA [Lemée et al, 2002] and DOC [Avril, 2002] .85 nM-eqFe) were of the same order of magnitude as the July value in our study (4.9 nM-eqFe). Seasonal variations of organic speciation have been demonstrated for copper [Croot, 2003] but, to our knowledge, this is the first report of the temporal variability of iron binding ligands at a yearly scale.…”
Section: Temporal Variation Of Iron Binding Ligand Concentrationssupporting
confidence: 67%
“…[dFe] [Bonnet and Guieu, 2006], TChla [Marty et al, 2002], BA [Lemée et al, 2002] and DOC [Avril, 2002] .85 nM-eqFe) were of the same order of magnitude as the July value in our study (4.9 nM-eqFe). Seasonal variations of organic speciation have been demonstrated for copper [Croot, 2003] but, to our knowledge, this is the first report of the temporal variability of iron binding ligands at a yearly scale.…”
Section: Temporal Variation Of Iron Binding Ligand Concentrationssupporting
confidence: 67%
“…This, however, was not possible in the low-UVR lake, since autotrophic picoplankton and bacteria co-existed in the < 3 µm fraction. Therefore, BCD in this lake was estimated by assuming that BR values lie within two limits: (i) a conservative value of 75 % of TPR, which is an average value based on data reported for oligotrophic waters (Lemeé et al, 2002), and (ii) a potential minimum value of 50 % of TPR (Robinson, 2008), comparable with direct measurements made in this study on the TPR vs. BR in La Caldera (Herrera et al, unpublished data).…”
Section: Analysis Of Biotic Functional Variablessupporting
confidence: 55%
“…It has also been demonstrated that UVR exposure in the upper layers of the water column can increase the proportion of photosynthate released as exudates (Carrillo et al, 2008;Korbee al., 2012), which would stimulate the growth of UVR-resistant bacteria (Xenopoulos and Schindler, 2003) and give rise to a coupled phytoplankton-bacteria relationship in clear oligotrophic lakes . Coupling between phytoplankton and bacterioplankton has been defined as the capacity of the carbon (C) released by phytoplankton to support the bacterial carbon requirement (Morán et al, 2002) and will therefore differ depending on (i) the availability of alternative (allochthonous or autochthonous) carbon sources (Gasol et al, 2009) and (ii) the supply of inorganic nutrients (Medina-Sánchez et al, 2010;López-Sandoval et al, 2011). Although the bacterial dependence on C released by phytoplankton is a well-established paradigm in aquatic microbiology (Cole et al, 1988), it is currently under renewed debate.…”
Section: P Carrillo Et Al: Synergistic Effects Of Uvr and Simulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…On an optimistic note, it should also be stressed that, in spite of all the problems and uncertainties mentioned, we have been able to identify patterns for some of the ecological key variables. As an example, pronounced seasonal dynamics in BP and BGE have been reported (Lemée et al 2002. If the current methods were not methodologically robust, we would not find such consistent patterns.…”
Section: How Accurately Are We Measuring Bacterial Activities?mentioning
confidence: 67%